Comparison of in vitro and in vivo Toxicity of Bupivacaine in Musculoskeletal Applications - Steverink, Jasper G.; Piluso, Susanna; Malda, Jos; Verlaan, Jorrit-Jan (Frontiers in Pain Research, 2021)
The recent societal debate on opioid use in treating postoperative pain has sparked the development of long-acting, opioid-free analgesic alternatives, often using the amino-amide local anesthetic bupivacaine as active pharmaceutical ingredient. A potential application is musculoskeletal surgeries, as these interventions rank amongst the most painful overall. Current literature showed that bupivacaine induced dose-dependent myo-, chondro-, and neurotoxicity, as well as delayed osteogenesis and disturbed wound healing in vitro. These observations did not translate to animal and clinical research, where toxic phenomena were seldom reported. An exception was bupivacaine-induced chondrotoxicity, which can mainly occur during continuous joint infusion. To decrease opioid consumption and provide sustained pain relief following musculoskeletal surgery, new strategies incorporating high concentrations of bupivacaine in drug delivery carriers are currently being developed. Local toxicity of these high concentrations is an area of further research. This review appraises relevant in vitro, animal and clinical studies on musculoskeletal local toxicity of bupivacaine.